IMPLEMENTASI KEBIJAKAN PENGEMBANGAN DAN PEMBANGUNAN PARIWISATA BERKELANJUTAN YANG BERBASIS KEARIFAN LOKAL DI BALI (Studi kasus: Desa Jatiluwih, Kabupaten Tabanan) - DWI WISMAYANTI, KADEK WIWIN (Jurnal Ilmiah Widya Sosiopolitika; Vol 2 No 1 (2020): ISU PARIWISATA DAN KESEHATAN DALAM PERSPEKTIF SOSIAL DAN POLITIK, 2020)
The implementation of tourism in Law No. 10 of 2009 in detail is explained in C hapter III of article 5 on the principle of the implementation of tourism. Stating that tourism is carried out with the principle of upholding religious norms and cultural values as an embodiment of the Tri Hita Karana concept; uphold human rights, cultural diversity and local wisdom; maintain the preservation of nature and the environment; empower the local community; ensuring integration between sectors, between regions, between the center and regions which constitutes a systemic unit within the framework of regional autonomy, as well as integration among stakeholders. Basically the organization of tourism in the village is aimed at improving the standard of living and welfare of the people through economic development through the development and development of sustainable tourism based on local wisdom. The implementation of tourism is then carried out by tourism institutions in order to create sustainable tourism development.This research is a type of descriptive qualitative research with data collection methods in the form of observation, interviews, and documentation. Informants in this study were determined through purposive techniques and snowball sampling. This research was conducted in Jatiluwih Village, Penebel District, Tabanan Regency. There are three indicators used in the study, namely: Implementation of policies consisting of Communication, Resources, Disposition, bureaucratic structures have been applied properly. Keywords: Policy implementation, sustainable tourism, local wisdom